Antimicrobial-drug use and changes in resistance in Streptococcus pneumoniae. - Diekema, D; Brueggemann, A; Doern, G (2000)
Resistance of Streptococcus pneumoniae to antimicrobial drugs is increasing. To investigate the relationship between antimicrobial use and susceptibility of S. pneumoniae isolates at 24 U.S. medical centers, we obtained data on outpatient antimicrobial-drug use for the regions surrounding 23 of these centers. We found an association between decreased penicillin susceptibility and use of beta-lactam antimicrobial drugs.